ДОКУМЕНТИ ІЗ ФОНДУ СТАЛІНА ПРО ОБСТАВИНИ ВЕЛИКОГО ГОЛОДУ В УКРАЇНІ (1932-1933 рр.) (Zaporizhzhia Historical Review, 2021)
The content of unique documents, that concern Holodomor in Ukraine in 1932-1933 and which are saved in the funds of the Russian archive of socio-political history, is analyzed in the article.